Robust and Flexible Optically Active 2D Membranes Based on Encapsulation of Liquid Crystals in Graphene Oxide Pockets. Issue 22 (27th October 2021) - Chen, Musen; Goh, Shan Min; Yang, Kou; Nikitina, Anna A.; Chen, Siyu; Leng, Xuanye; Karim, Nazmul; Hanson, Lindsay; Gleeson, Helen F.; Novoselov, Kostya S.; Andreeva, Daria V.
Abstract: Design and engineering of novel low dimensional metamaterials allow for new applications in membrane technology, aerospace and automotive industries, architecture, robotics, medicine, and textiles. Such materials can be strong, flexible, transparent, and can be assigned with different functionalities. Here, the authors explore the possibility of 2D graphene oxide (GO) surface to guide self‐assembly of 4‐cyano‐4′‐pentylbiphenyl (5CB) molecules via multiple hydrogen bonding and their clustering in optically active phases. The encapsulation of 5CB in a 2D geometry and birefringent properties of 5CB are tuned by the regulation of interaction energy between GO surface and 5CB. Chemical reduction of GO‐5CB composites results in electrically conductive reduced graphene oxide‐5CB membranes which change optical properties in response to Joule heating. The sustainable approach to the design of robust and flexible optically active materials will allow the formation of other metamaterials with different functionalities for advanced applications. Abstract : A new approach for the encapsulation of low molecular weight liquid crystals in graphene oxide nanosheets is proposed. The approach is versatile and adjustable for development of other robust and flexible metamaterials for aerospace and automotive industries, architecture, robotics, medicine, and textiles.